Nudging physical distancing behaviors during the pandemic: a field experiment on passengers in the subway stations of shiraz, Iran - Ramin Shiraly; Nika Khoshdel; Ali Khani Jeihooni; Mary-Louise McLaws (BMC, 2022)
Abstract Background The possibility of the emergence of new pandemics necessitates further research into using simple strategies to promote social distancing behaviors in public. Most of the current evidence on effectiveness of physical distancing interventions is based on self-report and measure of intention which will not necessarily predict actual behavior. Methods A field experimental study was conducted in the subway stations of Shiraz, Southern Iran. The interventions were based on intuitions from protection motivation theory and consisted of using environmental nudges to notify the passengers of the pandemic situation (threat appeal) and a verbal advice on keeping a safe physical distance as an effective method of protection against COVID-19 (coping message). Average physical distancing was estimated as the number of steps between two consecutive passengers and was compared between interventions (n = 1045) and the control (n = 855) groups. Results A total of 1900 people riding on subway escalators were directly observed during two intervention conditions and the control condition. Under either threat or coping-based interventions, passengers were two times more likely (OR 2.0, 95%CI 1.5-2.7, P <  0.001) to keep a physical distance of at least 1.2 m from the traveler in front compared with those who did receive no intervention. The Kruskal-Wallis test revealed that there was a significant improvement in physical distancing behaviors with coping advice compared with threat appeal and the control conditions (χ2 = 120.84, df = 2, p <  0.001). Conclusions Our findings suggest that simple and inexpensive theory-based interventions can be used in crowded public spaces to promote physical distancing within the context of the pandemic.